Dampak Keterlambatan Perbaikan Jembatan Pendem Terhadap Mobilitas Dan Aktivitas Masyarakat Di Kecamatan Jati Agung Kabupaten Lampung Selatan - Intan Rasita; Rizka Maydikta; Dini Apriliani; Mila Agustin; Abdul Halim (CV. SINAR HOWUHOWU, 2026)
This study examines how the delayed repair of the Pendem Bridge affects mobility and activities within the community of Jati Agung District, South Lampung Regency. The Pendem Bridge serves as a main route connecting the Karangsari and Fajar Baru communities, supporting economic, educational, social, and transportation activities. Delays in bridge repairs complicate access for residents, increase travel times, and endanger the safety of road users. A descriptive qualitative approach was used in this study, collecting data through field observations, document reviews, literature analysis, and interviews with local residents. The findings indicate that the delay in bridge repairs has impacted the distribution of goods, increased transportation costs, disrupted educational activities due to students arriving late for school, and reduced social interaction. Furthermore, the poor, muddy, and damaged road conditions increase the risk of accidents and cause inconvenience to users. Government actions include expediting bridge repairs, offering alternative routes, and installing safety signs. Meanwhile, the community plays a crucial role in maintaining and monitoring the condition of the infrastructure to ensure that damage is promptly addressed. This analysis demonstrates that adequate transportation infrastructure is crucial for ensuring efficient mobility, safety, and the advancement of socio-economic activities.